PENGARUH PENGGUNAAN MEDIA AUDIO VISUAL TERHADAP HASIL BELAJAR IPA SISWA KELAS IV SDN 05 2X11 KAYUTANAM - Hasnan Nafis (LP3M Universitas Muhammadiyah Muara Bungo, 2021)
This research was motivated by the low science learning outcomes, especially the fourth grade students of SDN 05 2x11 Kayu Tanam. This research is an experimental study with a research design Posstest Only Control Design. The population of this study were all students in grade IV A and IV B SDN 05 2x11 Kayu Tanam. The sampling technique in this study is total sampling. Data analysis, namely normality test, homogeneity test, and hypothesis testing. The results showed that tcount = 3.55, because tcount> ttable and this was not in Ho's acceptance so that Ha was accepted, meaning that learning using audio-visual media was better than conventional learning. It can be concluded that learning using audio-visual media has an influence on the science learning outcomes of fourth grade students of SDN 05 2x11 Kayu Tanam Padang Pariaman.